STRATEGI PEMASARAN JASA PENDIDIKAN DALAM MENINGKATKAN ANIMO MASYARAKAT DI MADRASAH TSANAWIYAH SWASTA MAMBA’UL ULUM KOTA JAMBI - Ma'arif, Muhammad Syamsul; Samsu, Samsu; Putra, Darma (Jurnal Manajemen Pendidikan, 2025)
This research aims to analyze the marketing strategies of educational services in increasing community interest at MTs Swasta Mamba’ul Ulum Kota Jambi. The study employed a descriptive qualitative method with data collected through observation, interviews, and documentation. The findings indicate that the marketing strategy of educational services at MTs Swasta Mamba’ul Ulum is implemented based on Kotler’s 7P service marketing mix. Product is reflected in the quality of graduates who possess noble character, memorize the Qur’an, and actively participate in religious activities. Price is set at an affordable level, adjusted to the economic capacity of parents. Place highlights the school’s location within the Islamic boarding school environment, which fosters a religious atmosphere. Promotion is carried out through direct approaches to the community, alumni networks, and religious activities. People involve professional and dedicated teachers, staff, and pesantren administrators. Process includes integrated intramural learning, extracurricular programs, and Islamic boarding school activities. Physical Evidence is demonstrated through the availability of adequate facilities such as classrooms, mosque, library, dormitory, and extracurricular amenities. Overall, the application of the 7P marketing mix has succeeded in strengthening public trust in the madrasah, even though the facilities are not yet fully modernized.